Psychological differences in food addiction and binge eating in a general Polish population - Jagoda Różycka; Ari Nowacki; Marta Łukowska; Maryla Sokołowska; Joanna Zielińska; Roksana Duszkiewicz; Monika M. Stojek (Scientific Reports)
Abstract The aim of the study was to identify the prevalence of food addiction (FA) and binge eating (BE) in a general Polish population, to explore the differences between these constructs, and to examine psychological differences among FA, BE, and FA + BE groups. 2123 participants completed the questionnaires: Yale Food Addiction Scale 2.0, Binge Eating Scale, The PTSD Checklist for DSM-5, Life Events Checklist, Adverse Childhood Experiences, Short UPPS-P scale (impulsive traits), Dutch Eating Behavior Questionnaire and Depression, Anxiety and Stress Scale − 21 items. 492 participants reported clinically significant symptoms of FA, BE, or both. Spearman’s correlations, Mann-Whitney U tests, and Kruskal-Wallis tests were performed to examine the relationships between variables. The present study showed that FA and BE symptoms are common in the adult sample. The FA, BE and FA + BE groups had higher scores than the control group for all variables included in the study. The FA + BE group presented a significantly higher level of behavioral and emotional symptoms, followed by the FA and the BE group with less severity of symptoms. This study supports the hypothesis of food addiction as a similar construct to BE. FA is a broader concept than BE, but individuals experiencing both indicated the greatest functional difficulties.